Working Capital Financing Education Through People's Business Credit (KUR) For Women MSME Entrepreneurs In Tanjung Inten Village, East Lampung Regency - Sastya Putri; Denny Kurniawan; Ilham Setio Wibowo; Harits Kurniawan (Devotion: Journal Corner of Community Service, 2026)
Limited working capital and limited knowledge of formal financing remain constraints for women-led micro, small, and medium enterprises (MSMEs) in rural areas. This community service activity aimed to provide education on People's Business Credit (KUR) as an alternative source of working capital financing for women MSME entrepreneurs in Tanjung Inten Village, East Lampung Regency. The activity used material presentations, discussions, and question-and-answer sessions covering the concept of KUR, the functions of working capital, general application requirements and procedures, productive use of funds, and repayment obligations. The activity was attended by [number of participants] women MSME entrepreneurs engaged in [types of businesses]. The activity expanded participants' access to information about KUR and opened discussion on requirements, collateral, installments, and application procedures. The education is expected to support more careful, productive, and responsible consideration of formal financing in accordance with business needs and repayment capacity.